KORELASI ANTARA KEMAMPUAN GURU MELAKSANAKAN PEMBELAJARAN DENGAN MEDIA KAHOOT DAN HASIL BELAJAR MENULIS TEKS KARYA ILMIAH SISWA SMAN 3 SINTANG - Winarti, Astuti (Universitas Tanjungpura, 2021)
ABSTRACTThis study aims to describe the correlation between the teacher's ability to carry out learning, hereinafter referred to as X1 and the ability to use kahoot media, hereinafter referred to as X2, with the results of learning to write scientific texts of students of SMAN 3 Sintang, hereinafter referred to as Y. The research method used is correlative with the form of quantitative research. The population in this study were students of class xi, and the research sample was 30 students. The data collection techniques used were indirect questionnaires and documentation. The data collection tools were questionnaire sheets and documentation. The results showed that there was a correlation between all variables. The significance between the variables X1 and Y is 0.024 which can be concluded that there is a correlation with a correlation coefficient of 0.411 which is at a moderate degree of relationship. The significance between the variables X2 and Y is 0.003, which can be concluded that there is a correlation with a correlation coefficient of 0.522 which is in the degree of moderate relationship. The significance between the variables X1 and X2 to Y is 0.007 which can be concluded that it has a correlation with a correlation coefficient of 0.552 which is at a moderate degree of relationship.Â Keywords: Teaching Ability, Kahoot Media, Learning Outcomes